ANALYSIS OF CEO TURNOVER IN INDONESIA: DOES UNDERPERFORMED ORGANIZATION CAUSE CEO TURNOVER? – CASES OF MERGER COMPANIES IN INDONESIA - Lindrianasari Lindrianasari; Nurdiono Nurdiono (Universitas Hayam Wuruk Perbanas, 2010)
The results of previous research on the relationship between organizational performance and CEO turnover have been inconsistent so far. It has shown that the lower the performance, the greater the likelihood of CEO turnover. This negative relationship has been found in many subjects in organization. On the other hand, some studies found a positive relationship between job performance and turnover (in which the higher the performance, the greater the likelihood of turnover). Using a measurement of longitudinal design, this research tested organizational performance, such as stock and financial performance of top management turnover among 129 target and non-acquired firms over a five-year period. This study found significant relationships between them. The results indicated that poor organization performance triggered CEO turnover in Indonesia, especially in merger firms. This result also have an implication for Indonesian business such how organizational performance can affect a merger or an acquisition and, as a straight forward, it also affects the management of an acquired company.